Performance Assessment of Construction Services Companies Based on Approach Balanced Scorecard Method (PT. Ganesha Praptama Karya Case Study) - Muhamad Dian Aryono; Riyadi Slamet; Priyawan Sunu (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
PT Ganesha Praptama Karya is still traditional, looking at financial aspects only for performance assessment. This research aims to design a performance assessment of construction companies that will be assessed based on the Balanced Scorecard method with four perspectives. This research uses a qualitative approach descriptively. This study's sampling method uses the random sampling method. The sample size for each questionnaire was 32 samples for the customer questionnaire and 58 people for the internal employee questionnaire. Based on the company's performance, a financial perspective shows that it can cover short-term debt before maturity with its current assets and can cover the costs incurred with the income earned. From the customer's perspective, the company's performance shows value quite well in terms of providing adequate service to customers so that it has a positive impact on the company. The company's performance, from an internal business perspective, is said to be quite good. This proves the company can provide sufficient equipment, facilities, and infrastructure. From the company's performance, learning, and growth perspectives, it can be said to be quite good. This proves the company can increase employee capacity through training as well as further education opportunities and a conducive work environment.